2013
DOI: 10.1371/journal.pgen.1003762
|View full text |Cite
|
Sign up to set email alerts
|

Two Portable Recombination Enhancers Direct Donor Choice in Fission Yeast Heterochromatin

Abstract: Mating-type switching in fission yeast results from gene conversions of the active mat1 locus by heterochromatic donors. mat1 is preferentially converted by mat2-P in M cells and by mat3-M in P cells. Here, we report that donor choice is governed by two portable recombination enhancers capable of promoting use of their adjacent cassette even when they are transposed to an ectopic location within the mat2-mat3 heterochromatic domain. Cells whose silent cassettes are swapped to mat2-M mat3-P switch mating-type p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 61 publications
0
69
0
Order By: Relevance
“…Regions controlling mating compatibility are in some cases associated with suppressed recombination while in other cases they harbor crossing-over hotspots (Burgoyne, 1982; Yi and Li, 2005; Hsueh et al , 2006; Brick et al , 2012; Sarbajna et al , 2012; Jakočiūnas et al , 2013; Bolton et al , 2014). The evolutionary drivers for these contrasted relationships between recombination and mating-type determination are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Regions controlling mating compatibility are in some cases associated with suppressed recombination while in other cases they harbor crossing-over hotspots (Burgoyne, 1982; Yi and Li, 2005; Hsueh et al , 2006; Brick et al , 2012; Sarbajna et al , 2012; Jakočiūnas et al , 2013; Bolton et al , 2014). The evolutionary drivers for these contrasted relationships between recombination and mating-type determination are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mc stimulates expression of a shorter transcript (swi2S) of the swi2 gene that facilitates mat2 utilization in M cells (58). However, in conflict with the spreading hypothesis, another study suggests that Swi2 binds directly to the mat2 cis-acting element in M cells (53).…”
mentioning
confidence: 97%
“…The switching to opposite mating-type was very inefficient (∼18%) in the h 09 strain, which suggests that the directionality is working correctly and that most switches result in homologous replacement. Recently, it was reported that cis-elements adjacent to mat2 and mat3, the Swi2-dependent recombination enhancer (SRE) adjacent to mat2 (SRE2), and SRE3 at mat3, govern the directionality (53). When mat2 and mat3 are swapped, accompanied by their respective SRE2 and SRE3 elements, the cells switch as efficiently as wild type, indicating that the SRE elements are critical for determining the donor choice.…”
mentioning
confidence: 99%
“…1). Despite their apparently independent origins, the switching systems of S. cerevisiae (3) and S. pombe (4, 5) have many parallels, including the presence of three MAT-like loci (two of which are silenced) with triplicated guide sequences, a mechanism for specifically inducing a DNA break at MAT, donor bias (27), and cell-lineage tracking. However, the details of switching and silencing are quite different in the two species (3,4).…”
mentioning
confidence: 99%